Recent Advances in Biosensors for Ovum Maturity Detection: Technologies, Challenges, and Future Perspectives - Zhao, Yuping (Exploring Science Academic Conference Series, 2026)
Biosensors are advanced medical detection tools with pivotal applications in ovum maturity detection, providing accurate clinical experimental data and professional condition assessment. This paper deliberates three main types of biosensors in this field: electrochemical sensors, which measure electronic signal changes via nano-modified electrodes to detect estradiol levels in follicular fluid, thereby assessing ovum maturity; optical sensors, which test the intensity of fluorescent biomarkers to evaluate t he dynamic change in mRNA; and piezoelectric sensors, which measure the changes in mass associated with ovum maturity.